2023
DOI: 10.1111/jan.15619
|View full text |Cite
|
Sign up to set email alerts
|

The academic stress and subjective well‐being of graduate nursing students: The mediating role of resilience

Abstract: Aim: To investigate the levels of subjective well-being in graduate nursing students, explore the impact of academic stress and resilience on subjective well-being, and examine the mediation effect of resilience on the relationship between academic stress and subjective well-being among graduate nursing students.Background: Few studies explore the impact of academic stress and resilience on subjective well-being among graduate nursing students. Understanding the status of subjective well-being and associated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
0
0
0
Order By: Relevance
“…The challenging demands of nursing education, woven with academic rigor, clinical complexities, and emotional challenges, require nursing students to have a strong foundation of resilience. A recent study highlighted the mediating role of resilience in strengthening nursing students' well-being and academic success [69]. A comprehensive integrative review found a robust positive relationship between social support and resilience among nursing students worldwide [70].…”
Section: Factors Associated With Nursing Students' Resiliencementioning
confidence: 99%
“…The challenging demands of nursing education, woven with academic rigor, clinical complexities, and emotional challenges, require nursing students to have a strong foundation of resilience. A recent study highlighted the mediating role of resilience in strengthening nursing students' well-being and academic success [69]. A comprehensive integrative review found a robust positive relationship between social support and resilience among nursing students worldwide [70].…”
Section: Factors Associated With Nursing Students' Resiliencementioning
confidence: 99%